THE IMPACT OF EXCHANGE RATE, VOLATILITY INDEX (VIX), AND JAKARTA COMPOSITE INDEX (JCI) ON BANKING STOCK RETURNS IN THE INDONESIA STOCK EXCHANGE - Syafrina Nabila; Erna Listyaningsih; Muhammad Irfan Pratama (Yayasan Multidimensi Kreatif, 2026)
This study investigates the impact of macroeconomic and global indicators—specifically the exchange rate, Volatility Index (VIX), and Jakarta Composite Index (JCI)—on banking stock returns in the Indonesia Stock Exchange (IDX). Utilizing a quantitative approach, this research employs a balanced panel data regression method, specifically identifying the Common Effect Model (CEM) as the most appropriate estimation technique. The sample consists of 60 observations derived from 15 consistently listed banking companies over the 2021–2024 period, using secondary data sourced from the IDX, Bank Indonesia, and the Chicago Board Options Exchange (CBOE).The empirical results demonstrate that both the exchange rate and the VIX have a significant negative effect on banking stock returns, indicating that Rupiah depreciation against the US Dollar and heightened global market volatility lower investor confidence and suppress stock performance. Conversely, the JCI exhibits a significant positive impact, reflecting that an optimistic domestic stock market environment significantly enhances banking stock returns. Furthermore, the analysis proves that the exchange rate, VIX, and JCI simultaneously exert a significant influence on banking stock returns, collectively explaining 59.55% of the variance in the dependent variable. These findings underscore that banking sector performance is deeply intertwined with a combination of domestic macroeconomic conditions and global capital market dynamics, providing essential insights for investors in optimizing their portfolios and for banking institutions in enhancing risk management strategies.